Design and simulation of force sensor with piezo resistive rectangular strain gauge - Thangamani, U.; Mohd. Yunus, Hamid; Ali, Chekima, Assoc. Prof. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/